The Effect of Individual Characteristics and Work Environment on Employee Performance at the Education Office of Pidie Jaya Regency - Herizal Herizal; Ismayli Ismayli; Busra Busra (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the factors that affect the performance of the employees of the Education Office of Pidie Jaya Regency by testing the individual characteristics and work environment variables. This study uses a sample of 84 employees with a total sampling method. The data analysis tool used is SPSS version 21 with multiple linear regression method. From the results of hypothesis testing simultaneously or as a whole, it is known that individual characteristics and work environment have a simultaneous or joint influence on the performance of the Pidie Jaya District Education Office employees. The results of the study on the influence of individual characteristics obtained the value oftcount8,683 greater thantable1,663with a probability of 0.00 less than 0.05, it can be interpreted as individual characteristicshas a partial and significant influence on the performance of the Pidie Jaya District Education Office employees.The results of the study on the influence of the work environment obtained the value oftcount3,894 greater thantable1,663with a probability of 0.00 less than 0.05, it can be interpreted that the work environmenthas a partial and significant influence on the performance of the Pidie Jaya District Education Office employees. From the two variables studied, it is known that individual characteristics play the most dominant role on employee performance at the Pidie Jaya District Education Office.